2007
DOI: 10.1029/2006jb004861
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric variations across the Superior Province, Ontario, Canada: Evidence from tomography and shear wave splitting

Abstract: [1] The Superior Province of the Canadian Shield is the largest contiguous region of the Archean crust. A combination of data from multiple experiments is used to obtain shear wave splitting parameters and a three-dimensional tomographic velocity model beneath a large portion of the Superior, corresponding approximately to the province of Ontario. Shear wave splits are obtained at 24 sites across the Superior, displaying strong (averaging 1.34 s) ENE-WSW splitting at stations west of 86°W and weaker (0.67 s) E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 56 publications
10
101
0
Order By: Relevance
“…Station WEMQ in the NW of the study area (∼53°N,78°W) is an obvious exception, exhibiting an extremely small stacked split, since almost all individual measurements at this station were nulls. A previous study using a much smaller data set [ Frederiksen et al , ] suggested a larger split; however, the large error bars reported for the splitting parameters suggest that a number of null measurements may have been present.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Station WEMQ in the NW of the study area (∼53°N,78°W) is an obvious exception, exhibiting an extremely small stacked split, since almost all individual measurements at this station were nulls. A previous study using a much smaller data set [ Frederiksen et al , ] suggested a larger split; however, the large error bars reported for the splitting parameters suggest that a number of null measurements may have been present.…”
Section: Discussionmentioning
confidence: 92%
“…Seismic anisotropy beneath eastern North America has been studied through measurements of S K S splitting for over 20 years [e.g., Vinnik et al , ; Barruol et al , ; Fouch et al , ; Eaton et al , ; Frederiksen et al , ]. A lack of seismograph stations throughout much of Quebec and the Atlantic provinces of Canada has left a large gap in coverage up to recent times; in contrast, the eastern U.S. and much of Ontario have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Weakened lithosphere associated with the failed Iapetan rift may have provided a path for hot spot magmatism in this region. Tomographic studies of the eastern Canadian lithosphere [e.g., Frederiksen et al , ; Villemaire et al , ] image a low‐velocity corridor in the upper mantle that correlates spatially with the Great Meteor hot spot track at the surface, also consistent with the injection of hot spot magmatic material into the lithosphere. The crustal thickness variations observed in this region may represent a reset tectonic signature rather than an original crustal feature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on geochronology of lower‐crustal xenoliths in the southern Superior craton south of Hudson Bay, Moser and Heaman [1997] document an episode of zircon growth interpreted to be caused by intrusion of magma into the lower crust during Proterozoic rifting of the craton. Like Hudson Bay, this part of the Superior craton is characterized by SKS splitting results that generally align with regional tectonic trends [e.g., Frederiksen et al , 2007]. Elsewhere, preferential reworking of the lower crust has also been attributed to magmatic underplating within a large igneous province in the Baltic Shield [ Kempton et al , 2001], mafic magmatism associated with dike swarms in the Slave craton [ Davis , 1997], and granulite‐facies metamorphism in the North China craton [ Liu et al , 2004].…”
Section: Discussionmentioning
confidence: 99%